2021
DOI: 10.1097/scs.0000000000007405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Alveolar Bone Quality: Correlation Between Histomorphometric Analysis and Lekholm and Zarb Classification

Abstract: Objectives: This study evaluated the bone quality of the maxilla and mandible by using the classification proposed by Lekholm and Zarb (L & Z) and histomorphometry. Methods: Sixty edentulous areas were evaluated. The classification by L & Z was obtained through the evaluation of periapical and panoramic radiographs associated with the surgeon's tactile perception during milling and implant installation. Before implant installation, bone biopsies of standardized sizes were performed for histological evaluation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
(101 reference statements)
1
8
0
Order By: Relevance
“…In the study results, short implants in the posterior area had similar bone stress and low risk of overloaded bone as "All-On-4" in the high bone quality mandible. In practice, the bone quality of the mandible is usually acceptable [ 41 ], and the use of short implants at the posterior is an alternative. Six or more implants give more options for restoration, such as segmented prostheses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study results, short implants in the posterior area had similar bone stress and low risk of overloaded bone as "All-On-4" in the high bone quality mandible. In practice, the bone quality of the mandible is usually acceptable [ 41 ], and the use of short implants at the posterior is an alternative. Six or more implants give more options for restoration, such as segmented prostheses.…”
Section: Discussionmentioning
confidence: 99%
“…In the study models with poorer bone quality, posterior areas showed a higher trend of bone resorption around short implants. The quality of maxillae, especially the posterior, is often unsatisfactory [ 41 ], which gives a warning for the use of short implants. Also, some clinical studies showed that short implants had a higher failure rate in the maxilla than in the mandible [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 6 pairs of samples (the extracted tooth and alveolar bone) were obtained from the lower jaw and only one sample originated from the upper jaw ( Table 2 ). It is also widely known that the bone density between the upper and lower jaw is markedly different, with the upper jaw being less dense and strong, but more vascularized than the lower jaw ( Oliveira et al, 2021 ). These aspects might be important in bone remodeling research and could be elucidated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of van Steenberghe and coworkers [ 15 ], patients received standard (pretapping the bone) and Mark II (self-tapping screw shaped implants, Nobel Biocare). Before implant insertion, a minimum bone height of 7 mm was required; each patient was classified according to the jaw bone resorption and bone quality of Lekholm and Zarb [ 20 ] quantified on CT scans. The total cohort of this study consisted of 399 patients, who received 1263 implants, from which, 27 implants were lost between 1- and 6-months post-insertion.…”
Section: Resultsmentioning
confidence: 99%